Nuisance Beaver Biology and Control in North-Central Wisconsin - Peterson, Ronald P. (University of Wisconsin-Stevens Point, College of Natural Resources, 1979)
From 1 June 1976 to 2 September 1977, a study was conducted in Oneida and Forest counties, Wisconsin to determine; 1) trends in the number, types, and sources of beaver damage complaints, and 2) the size, age and sex structure, and productivity of nuisance beaver colonies. About 700 beaver complaints for 1965-1977 were obtained from the study area. Sixty-eight beaver colonies were trapped, involving 166 beaver trapped and 42 colonies trapped out. A long-term increase in beaver complaints was related to increases in human and beaver populations. Road (41 percent), timber (32 percent), and lakeshore (11 percent) were the prevalent damage types. Road and railroad complaints were most recurrent; timber complaints were among the least recurrent. Private complainants were prevalent (46 percent) with government (35 percent) and commercial complainants (19 percent) comprising the remainder. Little change was noted in the relative percentages of either damage types or complaint sources. Of 56 beaver colonies, 66.1 percent were families, 19.6 percent were pairs, and 14.3 percent were singles. Number of beaver per trapped-out colony averaged 3.60; the mean for family colonies was 5.67. Of 166 beaver trapped, 34.3 percent were kits. Kits comprised 45.3 percent of the beaver from trapped-out colonies, suggesting that kits were under-represented in the entire sample. Yearlings (<1.5 years) also were under-represented. Annual mortality was 45.8 percent; kit and adult mortality was 73.1 percent and 23.2 percent, respectively. The sex ratio was about 1:1. Productivity increased and prenatal mortality decreased with age. Mean litter size was 3.41; prenatal mortality was 21.9 percent.